Chemical conversion of paper industry effluents into carboxymethylcellulose - Mastrantonio Garrido, Guido Enrique (2015)
The synthesis of carboxymethylcellulose was investigated using effluents containing short cellulose fibers. Car-boxymethylcellulose was synthesized according to the slurry process using different amount of sodium hydroxideand different incubation times at 30◦C after the etherification reaction as variables. Characterization of the prod-uct was conducted by Fourier transformed infrared spectroscopy, X-ray diffraction, degree of substitution, averagedegree of polymerization, water imbibing capacity, color, rheological properties, apparent viscosity and trace ele-ments content. Incubation time slightly increased the yield of the reaction and the degree of substitution duringthe first 12 h. The reaction yield and degree of substitution both decreased when the initially concentration of NaOHwas increased from 7.0 g/mL to 10.5 g/mL. The carboxymethylcellulose obtained was darker and had lower hydrationproperties than commercial samples. Trace elements content suggests that the product could be only used in paintfactories or building materials industries.